Prognostic Value of Atherosclerotic Extent in Diabetic Patients with Nonobstructive Coronary Artery Disease - Yipu Ding; Zinuan Liu; Guanhua Dou; Xia Yang; Xi Wang; Dongkai Shan; Bai He; Jing Jing; Yundai Chen; Junjie Yang (Journal of Diabetes Research)
Background and Objective. Atherosclerotic extent was proved to be associated with adverse cardiac events. Risk scores derived by coronary computed tomography angiography (CCTA) could identify high-risk group among patients with nonobstructive coronary artery disease (CAD), but the ability is still uncertain in the presence of diabetes mellitus (DM). The purpose of this study was to investigate the prognostic value of the atherosclerotic extent shown by CCTA in diabetic patients with nonobstructive CAD. Methods and Results. 813 DM patients (mean age 58.9±9.9 years, 48.1% male) referred for CCTA due to suspected CAD in 2015-2017 were consecutively included. During a median follow-up of 31.77 months, 50 major adverse cardiovascular events (MACEs) (6.15%) were experienced, including 2 cardiovascular deaths, 14 nonfatal myocardial infarctions, 27 unstable anginas requiring hospitalization, and 7 strokes. Three groups were defined based on coronary stenosis combined with Leiden score as normal, nonobstructive Leiden<5, and nonobstructive Leiden≥5. Cox models were used to assess the prognosis of plaque burden within these groups. An incremental incidence of MACE rates was observed. After adjustment for age, gender, and presence of high-risk plaque, the group of Leiden≥5 showed a higher risk than Leiden<5 (HR: 1.88, 95% CI: 1.03-3.42, p=0.039). Similar results were observed when segment involvement score (SIS) was used for sensitivity analysis. Conclusion. Atherosclerotic extent was associated with the prognosis of DM patients with nonobstructive coronary artery disease, highlighting the importance of better risk stratification and management.